A bibliometric analysis of core articles of international nursing research frontiers based on the Web of Science database - Han Shi-Fan; Cheng Jin-Lian; Wang Ya-Ping; Chen Qiong; Xu Zhu-Ya (Sciendo, 2020)
To review and analyze the basic information and distribution of core articles in the global research frontier of nursing, so as to ascertain the current trend in the field.